EFFECT OF DOMESTIC SEWAGE ON THE PHYSICO-CHEMICAL QUALITY OF RIVER RAPTI AT GORAKHPUR - MUGDHA AGRAHARI; VEENA B. KUSHWAHA (The Bioscan, 2012)
Present paper deals with fluctuations observed in physicochemical properties of water of river Rapti at Gorakhpur due to drainage of sewage into it. An increase in electrical conductivity, TDS, free CO2, bicarbonate alkalinity, total, Ca and Mg hardness, chloride, nitrate, phosphate, sulphate, BOD and COD while a decrease in pH, DO and carbonate alkalinity was observed at sewage mixing point. However, these parameters gradually changed at the station away from sewage mixing point (downstream) and were within the limits of Indian standards indicating river water safe for growth of aquatic life.